Comments on the paper by Mariusz W. Majewski published in Studia Historiae Scientiarum 17 (2018), pp. 89–117 - Paweł E. Tomaszewski (Studia Historiae Scientiarum, 2019)
Several remarks on the text by Mariusz W. Majewski devoted to the history of the Institute of Metallurgy and Metal Science at the Technical University of Warsaw, and on the role of Prof. Jan Czochralski, are presented. The aim was to show that the topic has not been exhausted, and some wordings need correction.